SYMBOLIC AND PROPHETIC SYNTAGMAS IN CHINUA ACHEBE’S ANTHILLS OF THE SAVANNAH - Omowumi Bode Steve Ekundayo; Abiola Olubunmi Akinbobola (English Review: Journal of English Education, 2016)
This essay discusses Achebe’s delineation of characters, events and use of language in Anthills of the Savannah (AS) as symbolic and prophetic syntagmas which later manifested in some real life personalities and socio-political phenomena in Africa and Nigeria, the setting of the novel. The primary source of data is Anthills of the Savannah. Secondary source and the internet were also consulted for the theoretical background and literature review. Grammatical structures and literary features were extracted and analyzed to show their associative and symbolic links with real life events which occurred after 1987, the year AS was published. The symbolic and prophetic syntagmas identified and their manifestations are presented with annotations in tables. The essay established that Achebe uses syntagmas of utterances, events, settings and characters to symbolize and foreshadow imminent events in the novel and socio-political occurrences in Nigeria and Africa, a feat which stands him out as a novelist with great prophetic insight and clairvoyance.Keywords: Achebe, AS, syntagma, prophetic, symbolic. character